Molecular Docking Evaluation of Cedrus deodara Secondary Metabolites as a Potent Anti-ovarian Cancer Agent - Priyadharshini Pillai (International Journal of Molecular Biotechnological Research, 2023)
Objective: According to the statistics for the year 2022 it was seen that cancer total cases is 14,61,427. After breast cancer, ovarian cancer is the second most frequent cancer among women. The estrogen receptor (PDB ID: 1X7E), progesterone receptor (PDB ID: 1A28), and Phosphoinositide 3-kinases (PDB ID: 4FJY) can be considered as target protein for ovarian cancer. The plant Cedrus deodara and its phytochemicals were chosen in this study to identify their pharmacological characteristics and the inhibitory effects against the target protein which is said to be involved in ovarian cancer. Infugem and Melphalan are FDA-approved ovarian cancer drugs. This drug is also chosen to compare the inhibitory effect of plant derivatives and the drugs. Methods: In this study, 30 phytochemicals were selected to know their binding affinity towards the protein targets.2 FDA-approved were also docked against all three target proteins. The target proteins were purified, and the missing residue was modeled using BIOVIA Discovery Studio then the protein structure analysis was also performed using PDBsum Generate. Using ADMETlab 2.0 pharmacological studies were performed. Result: The Oleanolic acid and 7beta-Hydroxydehydroabietic acid ligands showed the lowest binding affinity towards all three target proteins. By comparing the docking results of phytochemicals and FDA-approved drugs it is seen that the plant phytochemicals have the best binding affinity, and all the phytochemicals fulfill the criteria of ADMET analysis. Conclusion: According to the result observed from docking we can conclude that the ligands Oleanolic acid and 7beta-Hydroxydehydroabietic acid are showing inhibitory action against all three target proteins. Further In vitro study must be performed
Keywords: ADMET analysis; Cedrus deodara; molecular docking; ovarian cancer; phosphoinositide 3-kinases; progesterone receptor